2011
DOI: 10.1161/circgenetics.111.960146
|View full text |Cite
|
Sign up to set email alerts
|

The Coronary Artery Disease–Associated 9p21 Variant and Later Life 20-Year Survival to Cohort Extinction

Abstract: Background Common variation at chromosome 9p21 (marked by rs10757278 or rs1333049) is associated with coronary artery disease (CAD) and peripheral vascular disease. A decreasing effect at older age was suggested, and effects on long-term mortality are unclear. We estimated 9p21 associations with CAD and all-cause mortality in a CAD diagnosis–free older population. We also estimated classification gains on adding the variant to the Framingham Risk Score (FRS) for CAD. Methods and Results DNA was from an Estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
0
20
1
Order By: Relevance
“…47 This observation is remarkable, because of the presumed weaker effect of Chr9p21 in older populations (Table 1). 9 A metaanalysis in 6 prospective cohort studies showed that Chr9p21 was also associated with sudden and arrhythmic cardiac death, and controlling for cardiovascular and lifestyle risk factors strengthened this relationship (OR 1.29).…”
Section: Cardiovascular Mortalitymentioning
confidence: 96%
“…47 This observation is remarkable, because of the presumed weaker effect of Chr9p21 in older populations (Table 1). 9 A metaanalysis in 6 prospective cohort studies showed that Chr9p21 was also associated with sudden and arrhythmic cardiac death, and controlling for cardiovascular and lifestyle risk factors strengthened this relationship (OR 1.29).…”
Section: Cardiovascular Mortalitymentioning
confidence: 96%
“…9p21xSES Interaction and Coronary Artery Disease genes and the environment contribute to the cause of complex diseases. In case of 9p21.3 genetic variants, little consistent findings exist with reports of interaction by single risk factors such as age, 14,15 blood pressure, 16 smoking, 17 dietary intake, 18,19 glycemic control, 20 and abdominal obesity 21 in some study populations, but lack replication in others. [21][22][23] In most of these studies indicators of socioeconomic status (SES) have not been included although strong associations of SES with CAD and CAC have been reported that are partly being explained by socioeconomic differences in CVRF frequency.…”
mentioning
confidence: 74%
“…Adding 9p21 to the Framingham Risk Score may improve the targeting of CAD prevention in older people, but validation in independent samples is needed for confirmation. 33 …”
Section: Discussionmentioning
confidence: 99%